Hirshfeld surfaces identify inadequacies in computations of intermolecular interactions in crystals: pentamorphic 1,8-dihydroxyanthraquinone - Rohl, Andrew; Moret, M.; Kaminsky, W.; Claborn, Kacey; McKinnon, J.; Kahr, B. (American Chemical Society, 2008)
Fingerprint plots of Hirshfeld surfaces were used to locate and analyze the deficiencies in various methodologies employed in the determination of the relative energies of five polymorphs of 1,8-dihydroxyanthraquinone. Nine crystallographically independent molecules were characterized by X-ray crystallography and Hirshfeld surfaces were derived from the X-ray structures. The space groups and number of independent molecules (Z') for each of the polymorphs (1-5) is as follows: (1) P41 (or P43),Z' ) 1; (2) Pca21, Z' ) 2; (3) P1 j, Z' ) 4; (4) P21/n, Z' ) 1; (5) P41212 (or P43212), Z' ) 0.5. Form 1 is the most thermodynamically stable among the reproducible structures, as established by competitive solubility tests, followed by 2 and then 4. The unrestrained structures of the five polymorphs were computed using the CVFF and COMPASS force fields as well as with the density functionalcode, SIESTA.